Analysis of leading economic sectors on economic growth in Penajam Paser Utara regency - Widiya, Heni; Bina, Al (Indonesia Auditing Research Journal, 2025)
Economic growth is significantly important for every region, as it not only serves as an indicator of increased community income but also directly impacts the Local Revenue (PAD). The issues highlighted in this background emphasize the need for serious attention in managing both rapidly developing sectors and those experiencing saturation in Penajam Paser Utara Regency. The local government needs to identify the leading sectors in their area. The data used in this study includes annual Gross Regional Domestic Product (GRDP) and National Income (NI) for the year 2023. The data collection method employed in this research is secondary data. Based on the analysis results, it can be concluded that the Agriculture, Forestry, and Fisheries sectors are among the leading economic sectors in Penajam Paser Utara Regency. The local government of Penajam Paser Utara is also implementing policies to develop the Agriculture, Forestry, and Fisheries sectors, based on several strategies that include regional economic development policies, enhancing the role of the region as a motivator, facilitator, and mediator, as well as streamlining the licensing system in the industrial sector